2019
DOI: 10.1111/ocr.12304
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of facial skeletal asymmetry during foetal development using μCT imaging

Abstract: Structured Abstract Objectives Asymmetry has been noted in the human craniofacial region in several pathological conditional and growth abnormalities, often with a directional predilection. Physiological asymmetry has also been reported in normal adults and adolescents, with certain regions of the cranioskeleton, such as the mandible, displaying prevalent asymmetry. However, the timing at which such asymmetries arise has not been evaluated. The objectives of this study were to assess the degree of asymmetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Either types of data can be used in GM [10][11][12] and the latter is often used for the visualization of GM results. [13][14][15][16] Surface data represent "data on the object's surface," and are constructed as polygons. Surface data can be created by regional segmentation from volumetric data by stacking contours extracted from…”
Section: Preparation Of Image Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Either types of data can be used in GM [10][11][12] and the latter is often used for the visualization of GM results. [13][14][15][16] Surface data represent "data on the object's surface," and are constructed as polygons. Surface data can be created by regional segmentation from volumetric data by stacking contours extracted from…”
Section: Preparation Of Image Datamentioning
confidence: 99%
“…The volume data contain all information, including the inside of the objects, while the surface data contain only surface information, thus having less data. Either types of data can be used in GM 10–12 and the latter is often used for the visualization of GM results 13–16 …”
Section: Introduction To Gmmentioning
confidence: 99%
“…Also, we notice that individual landmarks do not have a clear definition of their position in some studies. 33,37,43 These discrepancies limit comparisons between individual landmarks with the same name among different studies.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Indeed, precise comparisons of lip fusion in several mouse strains (normal and cleft lip liable) found that the timing of when fusion was initiated was more variable in the cleft lip-liable strains ( Wang et al, 1995 ). There is also asymmetry of the jaw skeleton, derived from cranial neural crest cells in the normal human fetus ( Katsube et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%